Evaluation of carbonate accumulation, inorganic carbon content, and soil property changes in newly developed soils of degraded landscapes - Jabbarov, Zafarjon; Abdrakhmanov , Tokhtasin; Abdullaev, Shokhrukh; Makhammadiev, Samad; Nomozov, Urol; Rakhmatullaeva, Guljakhon; Kovácik, Peter (Journal of Degraded and Mining Lands Management, 2025)
The article examines the impact of inorganic carbon content on the soil pH environment, humus content, and the population of humus-decomposing microorganisms in newly formed soils on the dried bottom of the Aral Sea. The studies were conducted in 3 regions. The highest inorganic carbon content was 24.41% in the soils of Region III, while the lowest content was 9.18% in the soils of Region I. The inorganic carbon content in the soils affected the pH environment. In Region III, where inorganic carbon was more accumulated, the pH environment reached up to 8.6, indicating a higher alkalinity. In contrast, the soils of Region I, with lower inorganic carbon, had a pH of 7.1. The humus content also varied depending on the inorganic carbon content. In Region III, the humus content was 0.12%, while in Region I, it was 0.80%. The inorganic carbon content also influenced the number of humus-decomposing microorganisms. The results indicated that as the inorganic carbon content increased, the number of humus-decomposing microorganisms decreased. The results of the statistical analysis (LDA, PCA, Correlation, Regression, General statistics) are positive. Specifically, the F statistic is 657.5 (p<0.001), indicating that the analysis results are highly reliable and statistically significant. The study shows that inorganic carbon content in Aral Sea soils affects pH, humus levels, and humus-decomposing microorganisms, with higher carbon leading to higher pH and fewer microorganisms. Statistical analysis confirms reliability.